Pengaruh Likuiditas, Profitabilitas, Ukuran Perusahaan, dan Pertumbuhan Penjualan terhadap Financial Distress - Rizka Dwi Aryati; Risal Rinofah; Ratih Kusumawardhani (Universitas Batanghari Jambi, 2023)
This study aims to determine the impact of Covid-19 in terms of Liquidity, Profitability, Company Size, and Sales Growth on Financial Distress in tourism, restaurant and hotel sector companies listed on the IDX during the 2017-2021 period. The population of this study are companies in the tourism, restaurant and hotel sectors in the 2017-2021 period. In this study, Liquidity, Profitability, Company Size and Sales Growth are the independent variables, while Financial Distress is the research variable. From the results of the partial test (t test) shows that the variables Liquidity, Firm Size and Sales Growth have no effect on Financial Distress while the Profitability variable has a significant effect on Financial Distress because the sig value is 0.00 <0.005 and t count is 7.304 > t-table 1, 98761 Thus Profitability has an influence on Financial Distress.